2022
DOI: 10.3389/fgene.2021.804916
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Potential Role of LSM4 Overexpression in Hepatocellular Carcinoma: An Integrated Analysis Based on Multiple Databases

Abstract: Background: Hepatocellular carcinoma (HCC) is a solid tumor with high recurrence rate and high mortality. It is crucial to discover available biomarkers to achieve early diagnosis and improve the prognosis. The effect of LSM4 in HCC still remains unrevealed. Our study is dedicated to exploring the expression of LSM4 in HCC, demonstrating its clinical significance and potential molecular mechanisms.Methods: Clinical information and LSM4 expression values of HCC were obtained from Gene Expression Omnibus (GEO) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…High LSM4 expression enhanced ovarian cancer cell proliferation, metastasis and glycolysis 28 . LSM4 had increased expression in hepatocellular carcinoma and could serve as a diagnostic marker, which upregulation contributed to cell malignant behaviors 29,30 . Although LSM4 has been shown to be oncogenic in many cancers, its role in NSCLC progression has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…High LSM4 expression enhanced ovarian cancer cell proliferation, metastasis and glycolysis 28 . LSM4 had increased expression in hepatocellular carcinoma and could serve as a diagnostic marker, which upregulation contributed to cell malignant behaviors 29,30 . Although LSM4 has been shown to be oncogenic in many cancers, its role in NSCLC progression has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…The complex mechanisms in cancer cells have been extensively studied by researchers, but the available information is still far from sufficient [ 8 ]. The highly metabolically active nature of cancer, the over-activation of growth signals, and the unrestricted replication of cells have led us to ask the following questions: what on earth promotes the occurrence of cancer [ 9 11 ]? How do you kill cancer cells by inhibiting these mechanisms?…”
Section: Discussionmentioning
confidence: 99%
“…LSM4 is involved in the disease progression of pancreatic cancer by mediating the formation of U4/U6 snRNP [ 33 , 34 ]. Recent research by Chen et al suggested that LSM4 may affect the growth and transfer of HCC cells by regulating key pathways such as cell cycles, adhesive plaques, and metabolic-related pathways [ 35 ]. At present, the mechanism of action of LSM4 and LSM5 in lung cancer has not been reported.…”
Section: Discussionmentioning
confidence: 99%